2020
DOI: 10.25157/jpb.v8i2.4408
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA KONSEP SISTEM REPRODUKSI (Penelitian di Kelas XI-IPA SMA Terpadu Ar-Risalah)

Abstract: Latar belakang penelitian ini adalah: (1) kecakapan berpikir kritis belum ditangani sungguh-sungguh oleh para guru di sekolah, (2) masih rendahnya rasa ingin tahu siswa, sehingga siswa cenderung merasa cepat puas dengan apa yang mereka ketahui, dan (3) siswa masih jarang bertanya. Rumusan masalah dalam penelitian ini adalah bagaimanakah  pengaruh  model problem based learning terhadap keterampilan berpikir kritis siswa. Tujuan penelitian ini adalah  untuk mengetahui pengaruh penggunaan  model  problem based  l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Based on the analysis obtained, the increase in students' critical thinking skills is due to the PBL model providing opportunities for students to develop their critical thinking skills through complex problem-solving processes in small group discussions. In addition, the characteristics of the PBL model can support the achievement of increasing critical thinking skills because PBL has learning stages that provide space for students to think critically in finding concepts and solving problems related to the material presented by the teacher (Pujianti & Rusyana, 2020). This also aligns with Rusman's (2013) opinion, which states that problem-based learning is a learning approach used to stimulate higher-level thinking, including students' critical thinking skills in situations oriented to real-life problems.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the analysis obtained, the increase in students' critical thinking skills is due to the PBL model providing opportunities for students to develop their critical thinking skills through complex problem-solving processes in small group discussions. In addition, the characteristics of the PBL model can support the achievement of increasing critical thinking skills because PBL has learning stages that provide space for students to think critically in finding concepts and solving problems related to the material presented by the teacher (Pujianti & Rusyana, 2020). This also aligns with Rusman's (2013) opinion, which states that problem-based learning is a learning approach used to stimulate higher-level thinking, including students' critical thinking skills in situations oriented to real-life problems.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that the PBL model showed positive effect in improving students' critical thinking skills (Agnesa & Rahmadana, 2022;Dakabesi & Luoise, 2019;Hermawan, 2022;Kasmiati et al, 2020;Marhamah et al, 2020;Pusparini et al, 2021;Setiawan & Islami, 2020;Wenno et al, 2021;Windari & Yanti, 2021;Yulfiani & Muchlis, 2021). In addition, the effect of the PBL model on critical thinking skills was also found in the medium category (Pujianti & Rusyana, 2020). Based on the analysis obtained, the increase in students' critical thinking skills is due to the PBL model providing opportunities for students to develop their critical thinking skills through complex problem-solving processes in small group discussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berbagai macam keterampilan abad 21 yang perlu dikembangkan adalah communication (komunikasi), collaboration (kolaborasi), critical thinking (berpikir kritis) dan creativity (kreativitas) yang dikenal dengan 4C (Griffin et al, 2012). Tuntutan untuk menguasai keterampilan tersebut datang dari berbagai macam lulusan pada tingkat pendidikan yang masih kurang terampil untuk menggunakan keterampilan berkomunikasi, berpikir kritis, keterampilan etis dan profesional, kerja tim, bekerja dalam kelompok yang beragam, pengguna teknologi dan manajemen proyek serta kepemimpinan (Triling & Fadel, 2009) & Waris, 2019;Pujianti & Rusyana, 2020;Yani et al, 2021) telah menunjukkan bahwa pengembangan keterampilan berpikir kritis dapat dilakukan dengan mengimplementasikan model pembelajaran saat proses pembelajaran berlangsung di kelas. Keberhasilan proses pembelajaran yang berlangsung dilihat dari hasil tes keterampilan berpikir kritis.…”
Section: Pendahuluanunclassified
“…Critical thinking skill is very important to be mastered by students (Pujianti, 2020), because through critical thinking, students will be trained to observe the situation, raise questions, formulate hypotheses, make observations and collect data, then provide conclusions. Wahyuni in Lismaya (2021) stated that critical thinking also trains students to think logically and not to accept things easily.…”
Section: Introductionmentioning
confidence: 99%